Місце норм трудового права в системі правових засад соціальних гарантій військовослужбовців - Хортюк, Н. В.; Khortiuk, N. V. (Держава та регіони. Серія: Право. – 2022. – № 3 (77). – С. 200-205, 2022)
Здійснено комплексний аналіз норм загального та спеціального трудового законодавства, норми якого спрямовані на регулювання соціальних гарантій військовослужбовців в Україні. Аргументовано, що нормативно-правові акти у відповідні сфері найбільш доцільно поділити на: загальні та спеціальні. Констатовано, що саме норми трудового права займають ключове місце в системі правових засад соціальних гарантій військовослужбовців. Зроблено висновок, що нормативно-правові засади соціальних гарантій військовослужбовців знаходять своє закріплення у сукупності нормативно-правових актах різної юридичної сили.

The relevance of the article lies in the fact that the social protection of military personnel is one of the priority tasks of the Ukrainian state today. In this regard, Ukraine is currently developing a new system of social guarantees for military personnel, which, in turn, is taking place under the conditions of adaptation of our country’s legislation to the requirements and standards of the European Union and NATO. However, it would be fair to note that due to the implemented fragmentary changes, the system of social guarantees for military personnel still does not have a comprehensive nature and mostly does not meet the challenges of today. Therefore, the challenges facing the country require a scientific-theoretical rethinking and legislative improvement of the legal regulation of social guarantees for military personnel, in particular, the norms of the labor legislation of Ukraine. In the article, a comprehensive analysis of the norms of general and special labor legislation, the norms of which are aimed at regulating the social guarantees of military personnel in Ukraine, is carried out. It is argued that it is most expedient to divide normative legal acts in the relevant sphere into: general and special. It was established that labor law norms occupy a key place in the system of legal foundations of social guarantees for military personnel. It was concluded that the normative-legal foundations of social guarantees of military personnel are consolidated in a set of normative-legal acts of different legal force, which can be systematized according to the following criteria: 1) according to their legal force; 2) by industry affiliation (general norms of labor legislation and special norms regulating social protection and guarantees of its implementation for military personnel). However, despite such a wide range of legal acts, the key place in the system of relevant foundations is given to the norms of the labor field of law, because it is with their help: 1) the legal status of the military as subjects of labor law and social security law is fixed; 2) a regulatory basis is formed to ensure the equality of all categories of workers in the field of social protection; 3) the specifics of providing social guarantees for special subjects of labor law, - military personnel, are determined; 4) guarantees of wages, working hours, rest time, etc. are established; 5) the key forms and methods of implementing social guarantees are revealed; etc.

Проведен комплексный анализ норм общего и специального трудового законодательства, нормы которого направлены на регулирование социальных гарантий военнослужащих в Украине. Аргументировано, что нормативно- правовые акты в соответствующей сфере наиболее целесообразно разделить на: общие и специальные. Констатировано, что именно нормы трудового права занимают ключевое место в системе правовых основ социальных гарантий военнослужащих.
The place of norms of labor law in the system of legal foundations of social guarantees of military personnel
Keywords: норми трудового права; правові засади; правове регулювання; соціальні гарантії; військовослужбовці; norms of labor law; legal principles; legal regulation; social guarantees; military personnel; нормы трудового права; правовые основы; правовое регулирование; социальные гарантии; военнослужащие